Solitary fibrous tumor of the adrenal gland: a case report and review of the literature - Shi, Changjie; Shi, Xiuquan; Wu, Ding; Zhang, Ying; Fu, Dian; Xu, Xiaofeng; Cheng, Wen (Frontiers in Surgery, 2024)
Solitary fibrous tumor (SFT) is a rare mesenchymal tumor, probably of fibroblastic origin, mainly in the extremities and pleura. Primary SFT of the adrenal gland is clinically more rare. Here, we report the case of a 47-year-old woman who detected a left adrenal mass on physical examination, without any symptoms, and no laboratory abnormalities. A computed tomography (CT) examination of the adrenal gland suggested a round-like soft tissue density shadow in the left adrenal area. An unenhanced scan showed uneven density of the mass, with a scattered circular-like cystic low-density shadow inside, and an enhanced scan showed obvious uneven enhancement. We considered it to be adrenal pheochromocytoma. Ultimately, the patient was treated with laparoscopic left adrenalectomy. A pathological examination suggested an adrenal SFT. We reviewed previous case reports of adrenal SFTs and summarized the clinical characteristics of adrenal SFT combined with the relevant literature. For adrenal tumors with uneven low-density shadow and uneven CT enhancement features, we should consider the differential diagnosis of adrenal SFT.